Resveratrol: mudança do padrão de sinalização da SIRT 1 e AMPK durante o processo de envelhecimento - Camila Amaro Caldeira (2019)
Aging is primarily caused by the damage generated by free radicals (FR). The FR theory of aging postulates that reactions with these species are involved with agerelated disorders, such as cellular metabolic stress. Resveratrol (RSV), a polyphenolic compound has been shown to function as an antioxidant, antiinflammatory, anti-cancer, anti-diabetic. In the present study, the objective is to verify in an environment of oxidative stress (OS) in Human Mononuclear Cells of Middle aged and Elderly donors the existence of a change in the signaling pattern of SIRT1 and AMPK by RSV. In the Luminol-dependent chemiluminescence assay in the two age groups there was a significant reduction of the reactive oxygen species (ROS) in the cells stimulated with RSV. It was observed that in the Elderly group, there is a greater production of ROS and that this reduction from RSV was smaller compared to the other group. Results similar to those found in the Qualitative Fluorescence Microscopy Assay. In the Nitric Oxide (NO) test, there was no change in the amount of Nitric Oxide in peroxide (H2O2)-exposed cells and/or RSV-stimulated cells in the Middle age group. In the Elderly, a decrease (not significant) in the amount of NO was observed in cells exposed to the H2O2 that was restored by the stimulus with RSV. No change in Catalase activity was observed in the cells of the two age groups exposed to H2O2 and /or stimulated with RSV. A similar result was observed for the activity of Superoxide dismutase for Middle age. For the Elderly, there was an increase (not significant) in this activity in cells exposed to RSV. By the Luminoldependent chemiluminescence assay in the absence or presence of the inhibitors Sirtinol (for SIRT1) and Compound C (for AMPK), it was observed that for the Middle age group, the two routes have an antioxidant character and RSV acts via the SIRT1. In the Elderly, the SIRT1 pathway remains an antioxidant, but the antioxidant character of the AMPK pathway is silenced. RSV ceases to operate via SIRT1. We observed in this study that in aging there is a change in the cellular context characterized by the silencing of the antioxidant character of the AMPK pathway and there is alteration in the performance of the RSV, since its influence on the pathway of SIRT1 is ceased